Clinical and biological characterization of 20 patients with TANGO2 deficiency indicates novel triggers of metabolic crises and no primary energetic defect. Issue 2 (28th September 2020) - Bérat, Claire‐Marine; Montealegre, Sebastian; Wiedemann, Arnaud; Nuzum, Malou Le Corronc; Blondel, Amélie; Debruge, Hugo; Cano, Aline; Chabrol, Brigitte; Hoebeke, Célia; Polak, Michel; Stoupa, Athanasia; Feillet, François; et al.
Abstract: TANGO2 disease is a severe inherited disorder associating multiple symptoms such as metabolic crises, encephalopathy, cardiac arrhythmias, and hypothyroidism. The mechanism of action of TANGO2 is currently unknown. Here, we describe a cohort of 20 French patients bearing mutations in the TANGO2 gene. We found that the main clinical presentation was the association of neurodevelopmental delay (n = 17), acute metabolic crises (n = 17) and hypothyroidism (n = 12), with a large intrafamilial clinical variability. Metabolic crises included rhabdomyolysis (15/17), neurological symptoms (14/17), and cardiac features (12/17; long QT (n = 10), Brugada pattern (n = 2), cardiac arrhythmia (n = 6)) that required intensive care. We show previously uncharacterized triggers of metabolic crises in TANGO2 patients, such as some anesthetics and possibly l ‐carnitine. Unexpectedly, plasma acylcarnitines, plasma FGF‐21, muscle histology, and mitochondrial spectrometry were mostly normal. Moreover, in patients' primary myoblasts, palmitate and glutamine oxidation rates, and the mitochondrial network were also normal. Finally, we found variable mitochondrial respiration and defective clearance of oxidized DNA upon cycles of starvation and refeeding. We conclude that TANGO2 disease is a life‐threatening disease that needs specific cardiac management and anesthesia protocol. Mechanistically, TANGO2 disease is unlikely to originate from a primary mitochondrial defect. Rather, we suggest that mitochondrial defects are secondary to strong extrinsic triggers in TANGO2 deficient patients.